Analysis of Successfully Brand positioning & extending on customer engagement: A Study case of UNIQLO Retail Store - Naufal Oktavianissa (Eduvest - Journal of Universal Studies, 2024)
The study draws on relevant literature, observations, and interviews, revealing that efforts focused on positioning and customer engagement are often misunderstood as branding. UNIQLO, one of the world’s largest fashion apparel companies, integrates the entire process of clothing production, from planning and design to manufacturing, distribution, and retail. UNIQLO expanded its operations in Indonesia on February 13, 2013, and currently operates 65 stores across 25 cities in the country. This paper aims to explore how UNIQLO, a global fast-fashion retailer from Japan, drives its organizational success. UNIQLO is known for its high product quality, particularly through the introduction of its Heat Tech cold-weather underwear line, which is both affordable and suitable for warm climates. The company also continues to innovate through research and development to meet customer needs. UNIQLO's stores have a distinctive presence and strong market positioning. In 2014, the brand launched its mobile online store via a smartphone app, emphasizing customer satisfaction. This paper examines the key factors behind UNIQLO's organizational success.